Merger Performance and Managerial Incentives - Matthias Kräkel; Daniel Müller (University of Bonn, Bonn Graduate School of Economics (BGSE), 2014)
We consider a two-stage principal-agent model with limited liability in which a CEO is employed as agent to gather information about suitable merger targets and to manage the merged corporation in case of an acquisition. Our results show that the CEO systematically recommends targets with low synergies—even when targets with high synergies are available—to obtain high-powered incentives and, hence, a high personal income at the merger-management stage.
Keywords: D82; D86; G34; 330; acquisition; merger; moral hazard